Curbing Illegal Grazing Through Mediating Interests of Local Communities in East Nusa Tenggara Province, Indonesia - Kurniadi, Rahman; Maryani, Retno; Wibowo, Lukas Rumboko; Prasetyo, Budiyanto Dwi; Setyowati, Retno (Komunitas, 2020)
Communities living surrounding forest  have  used state forest for grazing area  in East Nusa Tenggara Timur Province, Indonesia for a long time.  However, Indonesia government have not given them a permit for managing state forest. Government will  involve communities in state forest management   to generate people income but government ,as a principal, was worried that the communities, as agent,  will act in the way contrary to the interest of government. We used  a principal agent theory to analyze principal agent problems which will occur if  communities manage  state forest for  silvopasture purpose. The research showed that there are some principal agent problems in silvopasture contract if government give communities a permit for silvopasture purpose, i.e.  communities, as agent, are  not willing  to plant trees and keep forest. Government must control communities to prevent some principal-agent problems in silvopasture contract.